1988
DOI: 10.1089/jir.1988.8.333
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Murine Cell Lines Expressing High, Intermediate, or Negative Levels of Surface Receptors for Interferon-γ

Abstract: Using radioiodinated murine interferon-gamma (IFN-gamma), various cell lines were analyzed for their capacity to bind IFN-gamma and to respond to its biological activity as measured by activation of the 2',5'-oligoadenylate (2-5A) synthetase, induction of the antiviral activity, and inhibition of [3H]thymidine uptake. A T-cell lymphoma, EL-4, was found to express relatively high number of specific membrane receptors for IFN-gamma (60,000/cell) with a dissociation constant of around 9 X 10(-10) M. By contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…The number of cells per well was estimated by counting the contents of identical wells put through the assay without labeled EN-y using trypsin to release the cells. Preliminary experiments established that under these conditions, equilibrium binding was achieved and that untreated M@ displayed 19000 receptor sites per cell with a Kd of 5.3 x consistent with that reported previously [26].…”
Section: Iodination Of Murine Rifn-y and Receptor Binding Assayssupporting
confidence: 85%
See 1 more Smart Citation
“…The number of cells per well was estimated by counting the contents of identical wells put through the assay without labeled EN-y using trypsin to release the cells. Preliminary experiments established that under these conditions, equilibrium binding was achieved and that untreated M@ displayed 19000 receptor sites per cell with a Kd of 5.3 x consistent with that reported previously [26].…”
Section: Iodination Of Murine Rifn-y and Receptor Binding Assayssupporting
confidence: 85%
“…Murine rIFN-y was iodinated using 12sI Bolton and Hunter's reagent as described by Fassio et al [26]. This procedure was reported to preserve biological activity and routinely yielded labeled IFN-y with a specific activity of about 2 pCi/pg.…”
Section: Iodination Of Murine Rifn-y and Receptor Binding Assaysmentioning
confidence: 99%
“…The specific activity of the iodinated IFN-y was -47 X lo3 cpm/ ng or 9,300 cpm/unit. Preliminary experiments with L929 cells indicated this iodinated IFN-y binds to its receptors with a KD of 1.2 X lo-'' M, which is similar to the published value (Fassio et al, 1988).…”
Section: Iodination Of Ifn-ysupporting
confidence: 85%
“…Based on the experiments using 1251-IFN-7 autoradiography, we conclude that the binding sites are distributed both on the cell bodies and on neurites of these cells. Receptor cross-linking data indicate a major protein species in the region of 100,000 daltons, which is similar to the results from the crosslinking of IFN-?/ to other murine cell types (Basu et al, 1988;Fassio et al, 1988). These findings strongly suggest that the effects of 1FN are on the neuronal cells directly.…”
Section: Temporary Rescue Of Neuronal Cells Deprived Of Ngfsupporting
confidence: 79%
“…A trivial explanation of the IFN resistance of these cell lines would be a possible absence of IFN receptors. However, Scatchard analysis revealed that the IFN-y-resistant T cell lines and the other IFN-y-responsive cell lines expressed similar numbers of receptors with similar Kd values [41]. Thus, to explain the cell specificity of the 2-5A synthetase gene activation, a few other hypothesis can be proposed, such as the absence in T lymphocytes of transcriptional factors recognizing consensus sequences in the 5' flanking region of the 2-5A synthetase gene.…”
Section: Discussionmentioning
confidence: 99%